Virosome: A vector in vaccine delivery - Karpe Shubham; Gupta Khushi; Vyas Ganesh; Rana Princy; Khan Fahad; Kumar Rajesh (BIO Web of Conferences, 2024)
These days vaccines are considered the best economical and effective technique for preventing and handling bacterial infections, like human papillomavirus (HPV) or meningitis, allergies, autoimmune Relevant Disorders, Microbial Infections, and many more viral diseases. Annually millions of lives are saved from death-causing infections and other relevant disorders with the help of proper immunization with the help of vaccines. But still, many diseases are not yet preventable by vaccines and there is a chance of the improvement of current vaccines with help of many approaches. One of these is a compound known as a virosome, which is produced when pure haemagglutinin and neuraminidase projections of the influenza virus surface are removed from viral envelope and deposited on the exterior of unilamellar liposomes.Studies have shown that in order to attain the desired therapeutic effect, a physical attachment between the target antigen and the virosomal carrier is necessary. A virosome can bind to and “infect” host cells and deliver the antigen directly into the processing pathway which is an Alternatively, the virosome may be phagocytosed by an APC. So Our review gives a novel idea of the vector technology for vaccine delivery, its properties, method of preparation, and importance as well as some applications of different virosomal vaccine discoveries.